Why do learners who draw perform well? Investigating the role of visualization, generation and externalization in learner-generated drawing. (April 2019) - Schmidgall, Steffen P.; Eitel, Alexander; Scheiter, Katharina
Abstract: In two experiments, we investigated which of the factors generation, visualization, and externalization mainly contribute to the benefits of learner-generated drawing. We also examined whether benefits of drawing were more pronounced in delayed rather than in immediate testing. To this end, Experiment 1 ( N = 121) focused on the comparison of the factors visualization and generation, whereas Experiment 2 ( N = 204) focused on the role of externalization in generative learning activities. In both experiments, participants were asked to read an expository text about biomechanics in human swimming behavior. In Experiment 1, participants were instructed either to construct drawings, to write summaries, to learn with multimedia material, or to only read. In Experiment 2, participants were instructed either to construct drawings, to mentally imagine the content, or to observe a multimedia presentation evolving gradually. Learning outcomes were measured with a recognition, transfer, and drawing test. In Experiment 1, the tests were administered immediately and after one week (within-subjects), whereas in Experiment 2 time of testing was manipulated between subjects. The results of both experiments revealed effects of experimental conditions for transfer and drawing performance, but not for recognition performance. Taken together, the findings indicate that visualization and externalization are the main contributing factors: The drawing and multimedia conditions outperformed the summary and text-only conditions (Exp. 1), thereby supporting the role of visualization, whereas the drawing and observation conditions outperformed the imagery conditions on the drawing test (Exp. 2), thereby emphasizing the role of externalization. There is little evidence that drawing constitutes a desirable difficulty. Highlights: Two experiments examined which factors mainly contribute to benefits of drawing on immediate and delayed test performance. The factors taken into account were visualization, generation and externalization. External visual representations (self-constructed or provided) improved learning whereas generation even hindered learning. The prognostic drawing effect was larger for higher-order than for lower-order assessments of test performance.